Laser synthesis of nanoparticles in organic solvents – products, reactions, and perspectives - Fromme, Theo; Reichenberger, Sven; Tibbetts, Katharine M.; Barcikowski, Stephan (Beilstein Journal of Nanotechnology, 2024)
Laser synthesis and processing of colloids (LSPC) is an established method for producing functional and durable nanomaterials and catalysts in virtually any liquid of choice. While the redox reactions during laser synthesis in water are fairly well understood, the corresponding reactions in organic liquids remain elusive, particularly because of the much greater complexity of carbon chemistry. To this end, this article first reviews the knowledge base of chemical reactions during LSPC and then deduces identifiable reaction pathways and mechanisms. This review also includes findings that are specific to the LSPC method variants laser ablation (LAL), fragmentation (LFL), melting (LML), and reduction (LRL) in organic liquids. A particular focus will be set on permanent gases, liquid hydrocarbons, and solid, carbonaceous species generated, including the formation of doped, compounded, and encapsulated nanoparticles. It will be shown how the choice of solvent, synthesis method, and laser parameters influence the nanostructure formation as well as the amount and chain length of the generated polyyne by-products. Finally, theoretical approaches to address the mechanisms of organic liquid decomposition and carbon shell formation are highlighted and discussed regarding current challenges and future perspectives of LSPC using organic liquids instead of water.
Keywords: alloy; photochemistry; pyrolysis; radicals; surface chemistry